Flexible management in industry as a factor of region’s sustainable development - E. V. Shestakova; A. M. Sitzhanova; R. M. Prytkov (Управление)
This article discusses the development of flexible management technologies in industry in current conditions. The main goal of the research is to study the features of functioning and develop a mechanism for the development of flexible technologies for managing industrial enterprises in Russia as one of the factors for the sustainable development of regions. Taking into account the goal set, the main tasks have been defined. It consists of studying the structure, a number of industrial enterprises by sectors, districts and the Russian Federation’s constituent entities; allocation of the varieties of flexible management technologies; development of a conceptual scheme and stages of the process of forming tools for the development mechanism of industrial enterprises based on flexible management technologies. The study used modern methods of collecting and statistical processing of initial information, in particular, the method of analytical groupings, the method of classifications and typologies, methods of economic, situational and system analysis. The paper deals with issues related to the analysis of the industrial production indices dynamics by entities of the Russian Federation. The problems are identified, the mechanism and stages of development of industrial enterprises have been formed on the basis of flexible management technologies. The main provisions and conclusions reflect the significance of the research and can be used by industrial enterprises in activities aimed at their development in the conditions of economic transformation. The authors’ recommendations will help to increase the competitiveness of enterprises, their sustainable functioning and development in the regions.